2022
DOI: 10.1097/cce.0000000000000740
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Selective Serotonin Reuptake Inhibitors With Delirium in Critically Ill Adults: A Secondary Analysis of the Bringing to Light the Risk Factors and Incidence of Neuropsychologic Dysfunction in ICU Survivors ICU Study

Abstract: To assess the association between selective serotonin reuptake inhibitors (SSRI) and delirium in the subsequent 24 hours after drug administration in critically ill adults. DESIGN: Retrospective cohort study utilizing the Bringing to Light the Risk Factors and Incidence of Neuropsychologic Dysfunction in ICU Survivors dataset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The percentage of patients in our sample receiving SSRIs (14.6%) is higher than the prevalence of antidepressant use prevalence in the general U.S. population (10%). 13,22 This echoes similar findings from prior work examining SSRIs in the critically ill. 16 This finding may reflect that patients requiring major surgery have a higher burden of mental health issues compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of patients in our sample receiving SSRIs (14.6%) is higher than the prevalence of antidepressant use prevalence in the general U.S. population (10%). 13,22 This echoes similar findings from prior work examining SSRIs in the critically ill. 16 This finding may reflect that patients requiring major surgery have a higher burden of mental health issues compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior retrospective cohort study, we demonstrated that SSRI administration may be associated with decreased risk of delirium on the same day of administration and at 24 hours in critically ill adults. 16 However, this work was limited by the inability to adjust for daily severity of illness. To further elucidate the relationship between SSRIs and delirium, we sought to examine the association of SSRIs and delirium incidence in a cohort of postoperative adults that have daily severity of illness measures.…”
Section: Introductionmentioning
confidence: 99%
“…Serotoninergic pathways from dorsal raphe nuclei play a central role in the maintenance of wakefulness and REM sleep suppression. Recent evidence points towards a protective role of selective serotonin reuptake inhibitors (SSRI) in ICU-related delirium [79]. Melatonin is the major regulator of circadian rhythm and, in the hospital setting, circadian misalignment is a recognized precipitating factor for delirium; moreover, the reduction of plasmatic levels of melatonin was associated with post-operative delirium [80].…”
Section: Discussionmentioning
confidence: 99%
“…for the development of delirium, a secondary analysis of the BRAIN-ICU study recently demonstrated that the use of selective serotonin reuptake inhibitors (SSRIs) was associated with a decreased risk of delirium and coma. 36,37 These findings warrant further exploration to determine the association between baseline mental illness, effective chronic treatment (i.e., SSRI therapy) versus new initiation during critical illness, and subsequent impact on delirium.…”
Section: While Baseline Anxiety and Depression Are Known Strong Risk ...mentioning
confidence: 99%
“…Again, the relationship between the underlying disease state (i.e., hypertension, either controlled or uncontrolled), effective medication therapy, and delirium warrants further exploration. While baseline anxiety and depression are known strong risk factors for the development of delirium, a secondary analysis of the BRAIN‐ICU study recently demonstrated that the use of selective serotonin reuptake inhibitors (SSRIs) was associated with a decreased risk of delirium and coma 36,37 . These findings warrant further exploration to determine the association between baseline mental illness, effective chronic treatment (i.e., SSRI therapy) versus new initiation during critical illness, and subsequent impact on delirium.…”
Section: Select Medications That May Impact Icu Deliriummentioning
confidence: 99%